Hotel Brand of Origin: Do Guests Perceive Service Differences? / Dwi Suhartanto - Suhartanto, Dwi (Universiti Teknologi MARA (UiTM), Malaysia, 2011)
This study reports an assessment of perceived service differences based on brand of origin (international and domestic brands) in the hotel industry. This study endeavours to extend recent advances in services marketing theory on service evaluation constructs: service quality, customer satisfaction, perceived value, brand image and brand loyalty at the international and domestic brand level of analysis. A total of 240 four-star hotel guests responded to the survey. The results suggest that international hotel guests perceived better service quality and brand loyalty compared with domestic hotel guests. The differences in how loyalty determinants affect brand loyalty persist across domestic and international hotel brands.